The Discursive Construction of Kiai’s Charisma in Indonesia: Power, Fantasy, and Religious Authority in Post-Reformation Pesantren - Akhmad Satori; Faisal Fadilla Noorikhsan; Ahmad Anfasul Marom (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
Studies on Kiai’s charisma have traditionally adopted essentialist or purely sociological perspectives, often neglecting how charisma is discursively constructed within post-Reformation political dynamics. This study offers an ontological rethinking of charisma, analyzing it as a partially fixed and contingent discursive construct. Specifically, it explores the discursive logic of charisma by examining political contestations and the role of fantasy in sustaining authority. Adopting a qualitative case study of a post-Reformation pesantren (Islamic boarding school) in Tasikmalaya, this research utilizes Poststructural Discourse Analysis (PDA) framed within Glynos and Howarth’s Logics of Critical Explanation. Data were gathered through in-depth interviews with followers and pesantren archives, subsequently coded using NVivo software. The empirical findings reveal that the Kiai's charisma is not an inherent trait but a structural capacity formed by articulating a "chain of equivalence" that unites student (follower) identity against secular modernization. Furthermore, followers' obedience is sustained by ideological fantasies of karamah (divine marvels) and barakah (blessings), which temporarily conceal their socio-psychological anxieties and unfulfilled desires. Theoretically, this study extends the application of post-structuralist discourse theory to traditional religious authority. Practically, it provides fresh insights into reading power relations within evolving traditional educational institutions.